Biomass Production and Uses - Jacob-Lopes, Eduardo; Queiroz Zepka, Leila (IntechOpen, 2015)
Biomass presents an authoritative and comprehensive overview of the possibilities for production and use of biomasses of agricultural and industrial importance. Issues related to environment, food, chemicals and energy present serious challenges to the success and stability of nations. The challenge to provide commodities to a rapidly increasing global population has made it imperative to find new technological routes to increase production of consumables while also considering the biospheres ability to regenerate resources. Plant and microbial biomasses are bioresources that may provide solutions to these critical challenges. Divided into five discreet parts, the book covers topics on production of unconventional biomasses and improving of conventional cultures, summarizing a range of useful products derived by biomass. This book provides an insight into future developments in each field and extensive bibliography. It will be an essential resource for researchers and academic and industry professionals in the life sciences.